2017
DOI: 10.1093/annonc/mdx235
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nivolumab benefit–risk profile of a 240-mg flat dose relative to a 3-mg/kg dosing regimen in patients with advanced tumors

Abstract: BackgroundNivolumab 3 mg/kg every 2 weeks (Q2W) has shown benefit versus the standard of care in melanoma, non-small cell lung cancer (NSCLC), and renal cell carcinoma (RCC). However, flat dosing is expected to shorten preparation time and improve ease of administration. With knowledge of nivolumab safety, efficacy, and pharmacokinetics across a wide dose range in body weight (BW) dosing, assessment of the benefit–risk profile of a 240-mg flat dose relative to the approved 3-mg/kg dose was approached by quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
171
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(183 citation statements)
references
References 14 publications
10
171
1
1
Order By: Relevance
“…However, for most of these antibodies, the estimated effect of BW on CL in their respective PopPK analyses had a coefficient ranging from 0.4 to 0.6, indicating the effect was less than proportional and both flat or BW‐based dosing will be suitable for these mAbs. Additionally, modelling and simulation studies using a range of mAbs have now suggested that BW‐based and flat dosing resulted in similar PK or pharmacodynamic variability, so BW‐based dosing does not always offer an advantage over flat dosing …”
Section: Discussionmentioning
confidence: 99%
“…However, for most of these antibodies, the estimated effect of BW on CL in their respective PopPK analyses had a coefficient ranging from 0.4 to 0.6, indicating the effect was less than proportional and both flat or BW‐based dosing will be suitable for these mAbs. Additionally, modelling and simulation studies using a range of mAbs have now suggested that BW‐based and flat dosing resulted in similar PK or pharmacodynamic variability, so BW‐based dosing does not always offer an advantage over flat dosing …”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab monotherapy was originally approved at a BWT‐ based dose of 3 mg/kg q2w, but the approved dose has recently been revised to 240 mg q2w or 480 mg q4w across multiple indications . Flat and less frequent dosing regimens can reduce the burden of frequent, lengthy intravenous treatments and allow combination of nivolumab with other agents with various dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Flat and less frequent dosing regimens can reduce the burden of frequent, lengthy intravenous treatments and allow combination of nivolumab with other agents with various dosing regimens. Based on PopPK modeling and exposure–response analyses for efficacy and safety, the benefit‐risk profile of the 240 mg q2w dose was determined to be comparable to the 3 mg/kg q2w dose . We extended this assessment in AdjMEL, and BIC post hoc estimates of exposures demonstrated that model predictions for the flat 240 mg q2w and the 480 mg q4w doses achieved comparable C avg ss (<1%) as the 3 mg/kg q2w dose.…”
Section: Discussionmentioning
confidence: 99%
“…2 Following the initial body weight-based approvals, the need for this type of dosing was reassessed for both pembrolizumab and nivolumab based on population PK modeling and therapeutic window information derived from exposure-response analyses, as well as demonstrated clinical safety at doses up to 10 mg/kg. 62,63 These assessments showed that 200-mg and 2 mg/kg doses provided similar exposure distributions for pembrolizumab and that the benefitrisk profile of nivolumab 240 mg every 2 weeks was comparable to 3 mg/kg every 2 weeks. Pembrolizumab was approved as a flat dose for all indications subsequent to melanoma, whereas in the case of nivolumab, modification of the initially approved 3 mg/kg every-2-week regimen to 240 mg every 2 weeks was approved by the FDA for melanoma, NSCLC, urothelial cancer, and RCC indications.…”
Section: Dosing Strategy (Flat Dosing Versus Body Weight-based Dosing)mentioning
confidence: 99%